2019
DOI: 10.5194/bg-2019-204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution and Flux of Dissolved Iron of the Rajang and Blackwater Rivers at Sarawak, Borneo

Abstract: <p><strong>Abstract.</strong> Dissolved iron (dFe) is essential for biogeochemical reactions in oceans, such as photosynthesis, respiration and nitrogen fixation. Currently, large uncertainties remain on riverine dFe inputs, especially for tropical rivers in Southeast Asia. In the present study, dFe concentrations and distribution along the salinity gradient in the Rajang River in Malaysia, and three blackwater rivers draining from peatlands, including the Maludam Rive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 67 publications
6
7
0
Order By: Relevance
“…The two fluorophores are typical of terrestrial input of DOM (Yamashita et al, 2008) and similar to observed fluorophores in other blackwater rivers in Borneo (Harun et al, 2015;Zhou et al, 2019). An increase in this C1/C2 ratio reflects a shift toward lower wavelengths and therefore toward lower aromaticity and lower molecular weight (Austnes et al, 2010;Zhou et al, 2019). Moreover, a decreasing trend in SUVA values is observed along Table 2.…”
Section: In-stream Processing Of Dom In Blackwater Riverssupporting
confidence: 72%
See 1 more Smart Citation
“…The two fluorophores are typical of terrestrial input of DOM (Yamashita et al, 2008) and similar to observed fluorophores in other blackwater rivers in Borneo (Harun et al, 2015;Zhou et al, 2019). An increase in this C1/C2 ratio reflects a shift toward lower wavelengths and therefore toward lower aromaticity and lower molecular weight (Austnes et al, 2010;Zhou et al, 2019). Moreover, a decreasing trend in SUVA values is observed along Table 2.…”
Section: In-stream Processing Of Dom In Blackwater Riverssupporting
confidence: 72%
“…The fluores- Table 1. cence index has relatively high values for tropical peatlands, where most of the DOM is of terrestrial origin (Gandois et al, 2014;Zhou et al, 2019). The FI values vary widely in the drainage canals (1.60 ± 0.17) and blackwater river (1.55 ± 0.06) but are more uniform in the whitewater river, both upstream (1.55 ± 0.03) and downstream (1.55 ± 0.05) of the confluence with the blackwater river.…”
Section: Dom Optical Characteristics and Stable Isotopic Signaturementioning
confidence: 99%
“…Malaysia is rich in peat swamp forests distributed across the various states with 23 percent retaining near-pristine nature; 17 percent are located in the state of Sarawak (Wetlands International, 2010). The state of Sarawak on the island of Borneo has the largest tropical peat swamp, thereby making Malaysia the second largest home to tropical peat swamp forests with an area of approximately 2.6 x 10 4 km 2 (Zhang et al, 2020). The establishment of major industries such as metal, food processing, electronics, petroleum, rubber, and textile in Malaysia (the mid-1980s) contributed to an increase in the deforestation rate in the country.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The establishment of major industries such as metal, food processing, electronics, petroleum, rubber, and textile in Malaysia (the mid-1980s) contributed to an increase in the deforestation rate in the country. The conversion of tropical peat swamp forests for agricultural purposes including rubber, oil palm, and sago plantations between 1990 and 2010 accounted for a 2 percent increase in the deforestation rate yearly in Sarawak (Zhang et al, 2020). Indonesia accounts for about 80 percent of the tropical peat swamp forests globally, although about 94,000 km 2 (above 36,000 square miles) have been lost due to anthropogenic activities (Dargie et al, 2017).…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation